A Mutant of Escherichia coli Defective in DNA Polymerase II Activity - Hirota, Yukinori (1972)
A mutant of E. coli defective in DNA polymerase II activity was isolated. Extracts had about 0.1% of the normal activity of the DNA polymerase. The effect of the mutation on the ability of cells to replicate DNA of various sources was analyzed. Mutant bacteria grow normally, at 41° as well as at 30°. All bacteriophages, F factors, and R factors examined so far grow normally in the mutant. Sensitivity of the mutant to ultraviolet radiation and alkylating reagents in growth media was the same as that of the wild type. The mutation, polB1, is recessive with respect to wild type. The polB1 mutation can coexist with recombination-defective mutations. Genetic mapping studies show the mutation to be located at about 2 min on the E. coli map.